A Rare Case of Meningoencephalo-Myelitis with a Tubercular Origin - Proma, Sanghita Banik; Hasan, Md Mehedi; Islam, Naylla; Saha, Arup Kumar; Amiruzzaman, (Bangladesh Journal of Medicine, 2023)
Tuberculosis (TB) can affect any bodily system including the central nervous system (CNS). CNS involvement in Tb is fairly uncommon with poor prognosis due to its high mortality and morbidity. Though meningoencephalitis is a frequent presentation of TB, myelitis along with it is rare. Due to the lack of detailed information about meningoencephalo-myelitis, the risk factors and prognosis of these patients are not fully understood. We report such a rare instance of tuberculosis involving the brain, meninges and spinal cord. The patient was a 13-year-old female with the complaints of fever, both lower limb weakness and urinary retention. The diagnosis was made based on the patient’s medical history and physical examination which showed meningeal syndrome, spinal cord and cranial nerve involvement. The diagnosis was confirmed by the analysis of cerebrospinal fluid, magnetic resonance imaging of the brain and spinal cord, and biochemical evidence of tuberculous infection. The patient had a marked clinical improvement and complete neurologic recovery after anti-tubercular treatment and high doses of systemic corticosteroids. The purpose of presenting the case is to share the bizarre presentation of CNS tuberculosis, a diagnostic and therapeutic emergency. Early diagnosis and immediate management may help with the unfavorable prognosis and our report hopes to shed light on it. J Medicine 2023; Vol. 34, No. 2(1) Supplement: 225